Parallel currencies in historical perspective - Lukas Von dem Berge (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2014)
[Introduction ...] To make the topic accessible to a bachelor thesis, and prevent the discussion from becoming too superficial, only a few representative parallel currency systems will be considered here. The second and third chapter will begin with a discussion of parallel currencies and currency competition throughout ancient, medieval, and modern Europe. Comparing the monetary history of Ancient Greece and Rome will illustrate the virtues of competing parallel currencies. A discussion of imaginary money' in medieval Europe will show that separation of the functions of money is a common feature of monetary history. The fourth chapter will look into flexible domestic exchange rates in China and Japan between the 17th and 19th century. The Chinese experience will demonstrate parallel currencies' ability to discover the boundaries of optimum currency areas, while the Japanese case will show how separating the functions of money can help protect agents from the detrimental effects of debasements. In the fourth chapter, the introduction of parallel paper currencies in America, such as the continentals and greenbacks, will be considered. These issues usually failed due to a lack of trust in the issuing authorities, illustrating the difficulties of introducing a weak parallel currency. Finally, the fifth chapter will discuss the role of stable and indexed parallel currencies as tools of monetary reform during hyperinflations - namely, the rentenmark in the German hyperinflation of 1932 and the tax pengö in the Hungarian hyperinflation of 1945/46. The conclusion will discuss the differences and communalities between the historical episodes. Last but not least, some tentative conclusions regarding the relevance of historical experience for the introduction of parallel currencies in the Eurozone will be drawn.
Keywords: 330